Prognostic value of minimal excitability of facial nerve in Bell's palsy. Issue 7 (July 1978) - Devi, S; Challenor, Y; Duarte, N; Lovelace, R E
Abstract : Nerve excitability is useful for prognosis in Bell's palsy. Minimal excitability values (MEV) were obtained by stimulating the facial nerve and recording the effective current (mA) required to evoke a minimal visible contraction of frontalis, orbicularis oculi, orbicularis oris, and mentalis muscles respectively. Serial MEVs were performed on 100 patients with facial palsy, of whom 87 were followed for six months or to complete recovery; 61 patients were treated with steroids of whom 57 had good recovery. Serial MEVs were not only useful for prognosis, but also helpful in regulating the dosage of prednisone.